STRATEGI KOMUNIKASI INSTRUKSIONAL GURU BAHASA INDONESIA DENGAN SISWA DI SMP AMAL MULIA KLAPANUNGGAL BOGOR - Gabena Siregar, Nofita Asyiah; Primasari, Winda (Fakultas Komunikasi, Sastra, dan Bahasa, 2015)
SMP Amal Mulia is a private junior high school standing in the Klapanuggal in 1999. The school is located in the residential neighborhood residents sunda, many students SMP amal mulia are used to communicating with sundanese therefore Indonesian teacher uses instructional communication strategies to increase students' language skills SMP Amal Mulia. This study reviews Instructional Communication Strategy with Student Teachers in SMP Amal Mulia in Klapanunggal Bogor. The purpose of this study was to analyze the instructional communication strategies used by Indonesian languange   teacher to improve students' language skills SMP. Besides analyzing instructional communication strategy, the authors also analyzes the process of message processing, the use of message communication, the use of instructional media and communication techniques and tactics used by Indonesian teacher. This research method is descriptive qualitative, the author explores instructional communication strategies used by Indonesian teacher. Information obtained through observation and depth interviews with key informants and informants. The results of this study illustrate that the instructional communication strategies used by Indonesian teacher is the gift of communication strategies (rewarding) and punishment (punishing). The processing of messages that are used to support the communication is processing   messages   expressive,   conventional,   and   rhetorical.   Media   is   often   used instructional tapes, videos, and training in the language lab. Instructional communication method used is the method of lecture, discussion and question and answer. Techniques and tactics used are small grouping technique and tactical use of communications with elements of humor. This strategy is used because it has received greater attention than other instructional communication strategy